2014
DOI: 10.1002/anie.201310908
|View full text |Cite
|
Sign up to set email alerts
|

Ozonated Graphene Oxide Film as a Proton‐Exchange Membrane

Abstract: Graphene oxide (GO) contains several chemical functional groups that are attached to the graphite basal plane and can be manipulated to tailor GO for specific applications. It is now revealed that the reaction of GO with ozone results in a high level of oxidation, which leads to significantly improved ionic (protonic) conductivity of the GO. Freestanding ozonated GO films were synthesized and used as efficient polymer electrolyte fuel cell membranes. The increase in protonic conductivity of the ozonated GO ori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
122
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 224 publications
(129 citation statements)
references
References 25 publications
5
122
0
Order By: Relevance
“…[12,16] Owing to the wide range of oxygen functional groups on its basal planes and edges, GO is also readily exfoliated to yield well-dispersed solution of individual GO sheets in both water and organic solvents, and then flow-directed assembled into a free-standing paper-like material by vacuum filtration. [12,17] However, despite all the progress of the development of a free-standing GO electrolyte membrane, its advantages are diminished with the difficulty to form a mechanically robust membrane.…”
mentioning
confidence: 99%
“…[12,16] Owing to the wide range of oxygen functional groups on its basal planes and edges, GO is also readily exfoliated to yield well-dispersed solution of individual GO sheets in both water and organic solvents, and then flow-directed assembled into a free-standing paper-like material by vacuum filtration. [12,17] However, despite all the progress of the development of a free-standing GO electrolyte membrane, its advantages are diminished with the difficulty to form a mechanically robust membrane.…”
mentioning
confidence: 99%
“…High-resolution TEM or STEM imaging can greatly help us understand the atomic structure and electronic properties of GO, although discrepancies have been observed among different reports. For example, stable images of GO were collected and shown under 80 kV electron beams [ 48 ], whereas in some cases only a maximum of 60 kV can be used for GO imaging [ 71 ]. In our experiments, we noticed GO is not stable under high-voltage beam (>60 eV).…”
Section: Transmission Electron Microscopy (Tem) and Scanning Transmismentioning
confidence: 69%
“…This work gave helpful insights on how GO researchers should store and preserve their GO samples to maintain the maximum level of oxidation. Another interesting protocol to overcome this degradation is by ozone treatment [ 71 ]. Gao et al reported the increased level of oxidation on degraded GO with bubbling of fresh O 3 into the GO dispersion in deionized (DI) water.…”
Section: Structure Degradationmentioning
confidence: 99%
“…4.16) [62]. It is important to note that in this work, the authors also discovered the proton-conducting behavior of hydrated GO films, which was later explored as a proton-exchange membrane in polymer electrolyte fuel cells [68].…”
Section: Go/rgos In Supercapacitorsmentioning
confidence: 75%